Develop Bactra system to determine Mutagens in the Environment, Food III: use emulators nitrogenous bases 5 - Bromeuruasil (Baghdad Science Journal, 2025)
The results show that the compound affects the rest of the living cells after treatment for 15 minutes The influence Almtafr has had the effect BU less than the effect of NTG in the case of the registration of every of Struptomaysan resistance and rifampicin, although the first attribute more responsive